Children's Emotional During Learning at Home in COVID-19 Pandemic - Ariani; Lilik Zuhriyah; Hajeng Wulandari; Ni Luh Putu Herli Mastuti; Sholihatul Amaliya; Adityas Ramadhani (Jurnal Kesehatan Islam : Islamic Health Journal, 2024)
Abstract The government policy of nationwide school closure to minimize the spreading of COVID-19 has affected over 80 million students in Indonesia. Understanding their emotions is essential because of their vulnerability, but it is still lacking in Indonesia. This study aimed to investigate emotional symptoms among children during learning at home. A cross-sectional online survey of 102 parents with children aged 6-18 years and their children who are learning at home. The survey was conducted in February 2021 in East Java province, Indonesia. Demographic information, emotional symptoms, and level of knowledge were assessed with a Strengths and Difficulty Questionnaire (SDQ). This research showed the rate of emotional problems among children is low and there is no relationship between the children’s age, education level, and knowledge level with the emotional symptoms in children (p > 0,05). The abnormal emotional symptoms are higher in middle school compared to other level schools and also higher in children aged 13-18 years old compared to 6-12 years old. The rate of emotional problems among children 6-18 years old is low, but this is essential to investigate because children are one of the vulnerable groups and older students are more likely to experience emotional symptoms. Keywords : Children, Emotional Symptom, Knowledge, Learning at Home